OSTEOPOROSIS PATOGENESIS DIAGNOSIS DAN PENANGANAN TERKINI - Kawiyana, I Ketut Sik (journal of internal medicine, 2009)
Osteoporosis is a bone metabolic disease, which is characterized by decreased bone mass due to reduced bone matrixand mineral, accompanied by micro architecture derangement of the bone tissue. Hence, in this disorder the bone has the tendencyto fracture due to low bone quality. Cell which responsible for bone formation is osteoblast, whereas osteoclast is responsible forbone resorption. In osteoporosis, bone turn over is abnormalwhichbone resorption is greater than bone formation. Thereforedirect factors for osteoporosis are number and activity of osteoclast in resorbing bone, and they are influenced by mediators andthe mediators depends on estrogen level. Number and activity of osteoclast cell are greater than number and activity of osteoblastcell in osteoporosis. This imbalance causes decreasing bone mass. The pathogenesis of osteoporosis has been discussed by showingthe recent theories related to increase of osteoclast cellÕs differentiation and activity due to: estrogen hormon deficiency,cytokine factor and axial loading. Several means in diagnosing the risks for osteoporosis and itÕs current managements based onitÕs pathogenesis have been mentioned too.